Characteristics of subpopulation composition of peripheral blood lymphocytes in children with different forms of congenital ichthyosis - D. G. Kuptsova; N. N. Murashkin; S. G. Makarova; R. A. Ivanov; K. O. Avetisyan; T. V. Radigina; O. V. Kurbatova; S. V. Petrichuk (Аллергология и Иммунология в Педиатрии)
.